2013
DOI: 10.1074/jbc.m112.404830
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Drosophila Heparan Sulfate 6-O-Endosulfatase in Sulfation Compensation*

Abstract: Background: HS sulfation compensation provides robustness to cellular signaling and animal development, but its mechanism is unknown. Results: Sulf1 is required for sulfation compensation in Hs2st mutants. Conclusion: Sulfation compensation depends on the coordinated activities of Hs2st, Hs6st, and Sulf1. Significance: The finding that Sulf1 is a novel component of HS sulfation compensation machinery provides novel mechanistic insight into this poorly understood phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…We have shown previously that the compensatory increase of 6-O-sulfation in Hs2st mutants is critical for the rescue of the mutants and that Hs2st; Hs6st double mutants fail to restore FGF, Wingless, and BMP signaling (4,5). Our disaccharide analysis data revealed a substantial increase 6-O-sulfation in Hsepi mutants as observed in Hs2st mutants (Fig.…”
Section: An Increase In 6-o-sulfation Is Critical For the Rescue Of Tsupporting
confidence: 70%
See 3 more Smart Citations
“…We have shown previously that the compensatory increase of 6-O-sulfation in Hs2st mutants is critical for the rescue of the mutants and that Hs2st; Hs6st double mutants fail to restore FGF, Wingless, and BMP signaling (4,5). Our disaccharide analysis data revealed a substantial increase 6-O-sulfation in Hsepi mutants as observed in Hs2st mutants (Fig.…”
Section: An Increase In 6-o-sulfation Is Critical For the Rescue Of Tsupporting
confidence: 70%
“…We showed that 6-O-sulfation is dramatically elevated in these mutants. Thus, compensatory up-regulation of 6-O-sulfate groups may be responsible for rescue of HS-dependent pathways in Hsepi mutant flies as observed in Hs2st mutant animals (4,5). Consistent with this idea, Hsepi; Hs6st mutants are completely lethal (Table 1).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…[15] As a result, natural polysaccharides that bind the HBD such as heparan sulfate (HS) have different binding properties for VEGF 165a and VEGF 165b. [9, 16, 17] Taking advantage of the structural differences between the HBDs, a therapeutic aptamer, pegaptanib, has been previously developed that only binds VEGF 165a . [18]…”
Section: Introductionmentioning
confidence: 99%